DOES THE AVAILABILITY OF DPP-4 INHIBITORS AFFECT THE GLYCEMIC CONTROL IN PATIENTS WITH TYPE 2 DIABETES MELLITUS? - Momani, Munther; Al Rawashdeh, Athar (Jordan Medical Journal, 2020)
Background: To investigate whether the availability of DPP-4 inhibitors (DPP-4I) affect the glycemic control in patients with T2DM. Methods: A total of 667 patients with T2DM were enrolled in this cross-sectional study. The patients were divided into two groups according to their medical insurance plans; the University (290 patients) and the Ministry (377 patients) groups. Both groups had comparable access to anti-diabetic medications except for DPP-4I which were available only to the University group. Accordingly, the University group was divided into two subgroups depending on their use of DPP-4I; DPP-4I users and non-users. Glycemic control, as assessed by HbA1C and rates of hypoglycemia, DKA and non-ketotic hyperosmolar state (NKHS), were compared in the three groups. Odds ratios were calculated to establish a correlation. Results: The rate of inadequate glycemic control (HbA1c ≥ 7%) was 72.3% in the University DPP-4I users, 51.5% in the University DPP-4I non-users and 59.9% in the Ministry group (p=0.003). After adjusting for various factors that influence glycemic control, the multivariate analysis showed that the University DPP-4I users were more likely to have inadequate glycemic control compared to those in the Ministry group (p=0.002, OR= 2.4). No significant difference was observed in the rate of hypoglycemia, DKA and NKHS in the three groups. Conclusion: Our results suggested that, in the studied population, the availability of DPP-4I did not improve glycemic control nor reduce the rate of acute complications of DM. On the contrary, inadequate glycemic control in the DPP-4I users was significantly higher compared to the non-users.